1999
DOI: 10.1002/(sici)1520-6300(199909/10)11:5<687::aid-ajhb11>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exclusion: Rates of hysterectomy and comparisons of age at natural menopause

Abstract: The objectives of this study were to identify factors related to history of hysterectomy; to evaluate whether or not subgroups with different rates of hysterectomy also report significantly different mean ages at natural menopause; and to consider how variation in rates of hysterectomy may affect intrapopulation and cross‐population comparisons of median ages at natural menopause. Data were drawn from a community sample in upstate New York. It is demonstrated that hysterectomy rates are not random with respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
2

Year Published

2001
2001
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
6
0
2
Order By: Relevance
“…One difference between our results and those of earlier studies is the overall low levels of education reported by women in the HHANES sample. For example, the effect of education on hysterectomy rates in upstate New York was most obvious between women who had stopped at a college education and those who had gone on to graduate school (Leidy, 1999). In our analyses, those who had finished 6 years of school were over one and one-half times more likely (odds ratio 1.622) to have had a hysterectomy than were those women who had fewer completed years of education.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…One difference between our results and those of earlier studies is the overall low levels of education reported by women in the HHANES sample. For example, the effect of education on hysterectomy rates in upstate New York was most obvious between women who had stopped at a college education and those who had gone on to graduate school (Leidy, 1999). In our analyses, those who had finished 6 years of school were over one and one-half times more likely (odds ratio 1.622) to have had a hysterectomy than were those women who had fewer completed years of education.…”
Section: Discussionmentioning
confidence: 67%
“…Contrary to the findings of Kjerulff et al (1993b), Leidy (1999), andMeilahan et al (1989), education increased the risk of hysterectomy. One difference between our results and those of earlier studies is the overall low levels of education reported by women in the HHANES sample.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…These results suggest that the timing of the onset of natural sterility varies little among populations, except in cases where sexual infectious diseases are widespread. Then, factors such as taboos against intercourse at older ages (Leidy, 1993), disease-induced sterility (Pennington and Harpending, 1991;Jenkins, 1993), or the use of contraception and sterilizations (Leidy, 1999;Barroso et al, 2003) can vary the values in human populations. In Tierra del Fuego, women who were sterilized showed an earlier age at last birth than natural menopausal women, but the differences were not statistically significant (Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…Johnston (2001) estimated a rate of surgical menopause of 43% among Blackfeet women of ages 50-69 years. Because hysterectomies are not random but are related to a woman's level of education and other social characteristics, studies that exclude women with hysterectomies may misrepresent the timing of menopause (Leidy, 1999). Further, many postmenopausal women take hormone replacement therapy (Brown et al, 2001); hence, the frequency of hot flash experience prior to interview is correspondingly low.…”
Section: Age At Menopausementioning
confidence: 99%